High-feed turning of AISI D2 tool steel using multi-radii tool inserts: Tool life, material removed, and workpiece surface integrity evaluation. Issue 6 (26th April 2017) - Khan, Sarmad Ali; Ahmad, Muhammad Aftab; Saleem, Muhammad Qaiser; Ghulam, Zakria; Qureshi, Muhammad Asif Mahmood
ABSTRACT: Multi-radii tool inserts offer novel configuration that comprises of multiple radii at tool nose. A review of the available literature indicates that there exists a need for experimental investigation on certain key machining characteristics of such tools. This paper reports on tool wear/life, material removed, and workpiece surface roughness when multi-radii mixed alumina TiN coated tool inserts are employed for turning D2 steel. Inserts of three different nose radii (0.40, 0.80, 1.20 mm) at six levels of feed rates (ranging from 0.157 to 0.562 mm/rev) are used. Results show that flank wear is the dominant wear mode with catastrophic tool failure occurring at highest nose radius (1.20 mm) and feed rate (0.562 mm/rev) combination. Also, there is ∼59% reduction in tool life accompanied by ∼62% increase in quantity of material removed as the feed rate increases from 0.157 to 0.562 mm/rev at maximum nose radius (1.20 mm). Feed rate is found to be statistically significant factor for all three responses considered herein at 95% confidence level. Surface integrity assessment at maximum feed rate reveals presence of a strain hardened layer extending to the depth of 150 µm below the machined surface without any observance of white layer for all the tool conditions and nose radius.